2013
DOI: 10.21608/ajas.2013.265365
|View full text |Cite
|
Sign up to set email alerts
|

Integration Between Bio, Organic and Mineral Nitrogen Fertilization and its Effect on Growth, Fruit Yield and Quality of Tomato ( Solanum lycopersicon L.)

Abstract: Two field experiment were carried out in the Experimental Farm of Sids Horticulture Research Station Beni-Sueif Governorate in summer seasons of 2011 and 2012 to study the response of tomato plants cv. (strain B) to microbein inoculation treatments, i.e. without , one dose at the time of transplanting or two doses at the time of transplanting and 20 days later and nitrogen fertilizer at the rates of 60, 80, 100 and 120Kg N/ fed combined with organic manure as compost at the rate of 4, 6, 8 and 10 t / fed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Singh [16,17] confirmed that humic acid works to increase the strength of vegetative growth of seedlings and the content of leaves of chlorophyll, as well as the breadth of the leaves and increase the height of the plant and the rate of increase in the diameter of the stem as well as the length of the branch and the number of lateral roots and chlorophyll content of the leaves. This is consistent with what was stated by [18][19][20][21][22][23] who indicated that the adding of humic acid to the mineral content of mango trees directed to an increase in the chlorophyll content in the leaves.…”
Section: Growth Regulator Triacontanol (T) Humic Acid (H) Mean )T) Hsupporting
confidence: 92%
“…Singh [16,17] confirmed that humic acid works to increase the strength of vegetative growth of seedlings and the content of leaves of chlorophyll, as well as the breadth of the leaves and increase the height of the plant and the rate of increase in the diameter of the stem as well as the length of the branch and the number of lateral roots and chlorophyll content of the leaves. This is consistent with what was stated by [18][19][20][21][22][23] who indicated that the adding of humic acid to the mineral content of mango trees directed to an increase in the chlorophyll content in the leaves.…”
Section: Growth Regulator Triacontanol (T) Humic Acid (H) Mean )T) Hsupporting
confidence: 92%
“…The reason may be attributed to the role of the nitrogen element contained in the nanofertilizer in increasing vegetative growth, which leads to a speedy process of photosynthesis and then an increase in manufactured sugars, thus increasing the percentage of total solid soluble substances in the tubers, in addition to the role The potassium element stimulates the materials resulting from the photosynthesis process and transfers them to tubers . [ 8,25 ] We conclude that the Arizona variety was significantly superior to the rest of the varieties in all the traits studied. As for the biofertilizer, it had a positive effect in increasing the chemical content of the tubers when treated with 10g of a mixture of bacterial biofertilizer and fungal biofertilizer.…”
Section: Starch Content In Tubers (%)mentioning
confidence: 88%
“…Nanotechnology is considered a good treatment of matter at the molecular or atomic level. This technology is promising in improving ongoing agricultural operations by improving agricultural production management [ 7,8 ] . It should be noted here that the current agricultural system in many countries of the world is characterized by declining productivity over time.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that higher nitrogen supplies brought about by biological nitrogen fixation contributed significantly to improved growth and assimilate accumulation, which in turn improved plant reproductive capacity and overall chickpea biomass. According to numerous authors (Ali et al, 2004;Elkoca et al, 2007;Togay et al, 2008;Dutta and Bandyopadhyay et al, 2009;Ahmed et al, 2010 andJakhar et al, 2016), inoculating chickpea seeds increased the supply of nitrogen significantly and had positive effects on reproductive performance, vegetative growth, and assimilate accumulation of plants. Least significant difference at p<0.05 and CV (%) = percentage of coefficient of variation.…”
Section: Interaction Effect Of Variety and Rhizobium Strain On Plant ...mentioning
confidence: 99%